Chemical Profile and Antioxidant Activity of Various Cysteine-Proteases' Impact on Spirulina Protein Hydrolysate - Djamaludin, Heder; Inayatussakinah, Inayatussakinah; Kusdiyarlistio, Andhika Alfanda; Armanda, Zidan; Dwijayanti, Dinia Rizqi; Maharsih, Inggit Kresna; Palupi, Kartika Dyah; Ferdian, Pamungkas Rizki; Elfirta, Rizki Rabeca; Notonegoro, Hartoyo (Indonesian Journal of Chemistry, 2025)
Spirulina is a type of microalgae that contains many useful compounds having antioxidant properties. It has low biological activity and limited protein content when used in dry form. Proteins can be broken down through a hydrolysis reaction to increase their bioactivity, producing smaller peptides and free amino acids. This study aims to evaluate the effects of two cysteine-protease enzymes, bromelain and papain, on the hydrolysis of Spirulina protein. The research examined how these enzymes affect the degree of hydrolysis, protein content, molecular weight, and antioxidant activity of the resulting protein hydrolysate. A non-factorial, completely randomized design was used with three replicates per treatment. The results showed that the type of enzyme used significantly influenced all measured parameters. Bromelain was found to be more effective than papain. Spirulina protein hydrolyzed with bromelain had 32.15 ± 0.74% protein, 48.51 ± 0.94% hydrolysis, a density of 0.786 mg/mL, and 29.64 ± 0.82 ppm antioxidant activity. It also contained 18 types of amino acids, totaling 14.41 g/kg. The most efficient of physical extraction methods—particularly the combination of freeze-thaw and ultrasonication—for obtaining high-yield, high-quality protein from Spirulina. Further purification is needed to obtain the smallest peptide.